Manuel Prado and the Economic Liberalism in Peru - Sato Kuroda, Enrique (2005)
The article is a review of some fundamental writings by Manuel Pardo, complemented with articles by Manuel Atanasio Fuentes and Luis Benjamín Cisneros, in an attempt to approach the economic liberal thought of the second half of the 19th century; especially his vision of development, some state intervention and the integration of the Adine population into the market.